+0  
 
+1
49
5
avatar+95 

Simplify 2(3sqrt9)/1 + 3sqrt9 + 3sqrt9

 

I got 3 - 3sqrt9 and -6 but -6 is wrong and 3 - 3sqrt is unsimplified

 Jun 30, 2023
 #1
avatar
0

Why not: 2 * (3 * 3) + (3*3) +(3*3)=36

 Jun 30, 2023
 #2
avatar+95 
+1

Because these are cube roots so it's cube root of 9 

 Jun 30, 2023
 #3
avatar
-1

Simplify 2 * (9)^(1/3) + 9^(1/3) + 9^(1/3)

 

4 * 3^(2/3)

 Jun 30, 2023
 #4
avatar+95 
+1

Cube roots mean that it takes three numbers to get that one number

 Jun 30, 2023
 #5
avatar
0

Simplify 2 * (9)^(1/3) + 9^(1/3) + 9^(1/3)

 

==2 * 3^(2/3) + (1 * 3^(2/3)) + (1 * 3^(2/3))

 

==[2 + 1 + 1] * 3^(2/3)

 

==4 * 3^(2/3)  [this is the same as:]

 

==4 * 9^(1/3)

 Jun 30, 2023

3 Online Users

avatar
avatar
avatar